Vanadium-basidiomycete fungi interaction and its impact on vanadium biogeochemistry. (September 2019) - Xu, Yu-Hui; Brandl, Helmut; Osterwalder, Stefan; Elzinga, Evert J.; Huang, Jen-How
Abstract: Fungi are well known to strongly interact with metals, thereby influencing metal biogeochemistry in the terrestrial environment. To assess and quantify potential fungi-vanadium (V) interactions, Amanita muscaria, Armillaria cepistipes, Xerocomus badius and Bjerkandera adusta were cultured in media containing soluble V (VOSO4 or NaVO3 ) or solid-phase V of different chemical forms and oxidation state (V2 O3, VO2, V2 O5, or V-Ti magnetite slag). All fungi underwent physiological and structural changes, as revealed by alterations in FT-IR peak positions and intensities relative to the control, and morphological changes of mycelia, as observed by scanning electron microscopy. The diametric growth size generally decreased with decreasing oxidation state of V and with increasing concentrations of VOSO4 and NaVO3, implying that V toxicity is dependent on V speciation. The tolerance index, the ratio of treated and control mycelium (dry weight), shows different tendencies, suggesting additional factors influencing fungi weight, such as the formation of extrahyphal crystals. Vanadium accumulation from VOSO4 and NaVO3 medium in all fungi (up to 51.3 mg g −1 ) shows the potential of fungi to immobilise soluble V, thereby reducing its impacts on environmental and human health. Uptake and accumulation of V in slag was insignificant, reflecting the association of slag V with insoluble crystalline materials. The fungal accumulation of V in medium amended with V-oxides demonstrates the ability of fungi to solubilise solid-phase V compounds, thereby introducing previously immobile V into the V biogeochemical cycle and into the food chain where it may impact ecological and human health. A. muscaria lowered the pH of the medium substantially during cultivation, indicating acidolysis and complexolysis via excretion of organic acids (e.g. oxalic acid). Oxidation of VOSO4 was observed by a colour change of the medium to yellow during B. adusta cultivation, revealing the role of fungally-mediated redox transformation in V (im)mobilisation. The calculated removal efficiencies of soluble V were 40–90% for A. cepistipes and X. badius, but a much lower recovery (0–20%) was observed from V oxides and slag (0–20%) by all fungi. This suggests the probable application of fungi for bio-remediation of mobile/soluble V in contaminated soils but not of V incorporated in the lattice of soil minerals. Highlights: Tolerance against vanadium depends on fungi species and vanadium speciation Vanadium exposure may lead to physiological and structural changes of fungi Fungi may solubilise mineral vanadium and trap soluble vanadium for accumulation Application of fungi may be suitable for remediation of soluble vanadium in soils